PERBANDINGAN BAHASA SURAT PEMBACA DALAM MAJALAH KAWANKU DAN HAI - Adhani, Agnes (Widya Warta, 2010)
The background of this research was due to the fact that communication processes involve two sides â€“ speakers and hearers, in which the delivered massages are tied within discourses. Letters from readers, as a means used by readers to express â€œsomethingâ€ to mass-media management or other readers, are in line with mass-media characteristics. â€œKawankuâ€, a magazine for female teenagers with its motto: â€œunbeatable fun girlâ€ and â€œHaiâ€, a magazine for male teenagers with its motto: â€œkarena kita luar biasaâ€ have certain similarities and differences in their language use. This study aimed to compare the topic, language use, and communicative acts in letters from readers found in the magazines â€œKawankuâ€ and â€œHaiâ€. The research was descriptive in nature. It described the data â€“ 60 letters from readers in Chit-Chat â€œKawankuâ€ and 58 letters from readers in Memo â€œHaiâ€, which comprised 10 editions of each magazine namely, no. 40 up to no. 49 published in September â€“Â  Desember 2007. The data analysis showed (1) due to the topic, domestic artists/celebrities and foreign music groups were dominant in â€œKawankuâ€; while, opinions and the contents of the magazine were dominant in â€œHai", (2) concerning the language use, especially theÂ  orthographic writings, the titles of the letters in â€œKawankuâ€ were writtenÂ  in small letters; whereas, those in â€œHaiâ€ were written in capital letters; the use of colloquial language was of no distinction in the two magazines; the use of abbreviations and acronyms in â€œHaiâ€ was striking, such as SMS; the use of foreign language was rather different in the two magazines. Japanese was used in â€œKawankuâ€, but â€œemoticonsâ€ was used in â€œHaiâ€, (3) in relation to communicative acts, courtesy was maintained in â€œKawankuâ€; it was realized with opening and closing greetings; meanwhile, in â€œHaiâ€ the intention of letters was stated straightforwardly and there were criticisms as well as severe complaints.